Cross-Border Equity Market Integration and Corporate Investment Efficiency: Evidence from China’s Stock Connect - Nasriddinov, Bobur; Guosong, Wang (European Scientific Journal, ESJ, 2026)
This paper investigates a fundamental empirical question in international finance: when stock markets become more connected across borders, does that actually push companies to make better investment decisions? To examine this, China’s Stock Connect program, encompassing the Shanghai-Hong Kong and Shenzhen-Hong Kong channels, is used as a real-world test case. These programs serve as a quasi-natural experiment to identify the causal effects of foreign investor participation. What makes this setup useful is that it allows foreign investors to trade shares in certain Chinese companies without changing how those companies are run internally, so any behavioral shifts can be traced back to market integration itself. Drawing on data from Chinese publicly listed companies between 2010 and 2023, the study measures how far each firm’s investment decisions stray from the optimal level. Through regression analysis controlling for individual company characteristics and broader yearly trends, the paper tracks what happens to firms once they join the program. The empirical analysis uses firm and year fixed effects models together with an event-study framework to examine how investment behavior evolves before and after firms gain access to cross-border investors. The findings are fairly clear: companies that joined the cross-border trading program became noticeably better at allocating capital compared to those that didn’t. The improvement unfolds gradually rather than immediately, suggesting firms need time to adjust to new investor dynamics. These findings hold up across different measures of investment efficiency and different sample configurations. Overall, this study offers a firm-level perspective on the real effects of financial integration at the firm level. It shows that opening equity markets to a broader pool of international investors can meaningfully improve how companies deploy their resources.